IDENTIFIKASI MASALAH PENYEDIAAN AIR BERSIH DI IBUKOTA KABUPATEN KUTAI BARAT DAN ALTERNATIF PEMECAHANNYA - Rahardjo, Petrus Nugro (Jurnal Teknologi Lingkungan, 2004)
As the capital city of West Kutai Regency, Sendawar still has a lot of problems relating to clean water supply for its residence. Those problems are caused by the very limited capability of local water authority (PDAM), the worse of environment management and water pollutions. Water pollutions occur because of improper mining activities (gold, silver and coal), domestic wastewater and sediment particles affected by increasing run off coefficient and erosion. Therefore the quality of surface water (River Mahakam) becomes worse and worse. PDAM Problems are not only being able to serve clean water need just for 19% residence in Sendawar, but also the low capability of human resources. There are three ways to solve those problems. Firstly, it is very important to apply a concept “One River One Management” in the Mahakam Catchment Area. Secondly, Application ofwastewater treatment technology must be carried out to reduce the pollutants produced from mining industries and municipal area. The third is by improving the human resource quality, especially in the field of environment and sustainable development.